Active play for special needs: The impact of running and jumping games on motor skills in children with intellectual disabilities - Raharjo, Slamet; Yunus, Mahmud; Andiana, Olivia; Subagio, Irmantara (Jurnal Ilmu Keolahragaan, 2025)
Background. Children with intellectual disabilities generally experience impairments in motor skills, movement coordination, physical health, and environmental awareness. Therefore, effective play-based therapy to improve motor impairments in children with intellectual disabilities is highly needed. Objectives. This study aims to examine the effect of a running and jumping game model in improving motor impairments in children with intellectual disabilities. Methods. This study used a pre-experimental design involving male children with intellectual disabilities aged 11"“12 years as research subjects. The running and jumping game model was implemented for 30 minutes per session, three times a week, over a period of four weeks. Data were collected by measuring motor development indicators, specifically running speed and jump height, before and after the intervention using a 40-meter sprint test and a vertical jump test. Data were analyzed using the paired sample t-test with a 5% significance level. Results. The results showed a significant improvement in running speed between the pretest and posttest (8.98 ±0.07 vs. 7.66 ±0.09 seconds; p=0.001). Similarly, there was a significant difference in jump height between the pretest and posttest (21.57 ±0.98 vs. 31.43 ±1.72 cm; p=0.001). These findings indicate that the running and jumping game model is effective in improving motor impairments in children with intellectual disabilities. Conclusion. Based on the results, it can be concluded that implementing the running and jumping game model three times a week for four weeks is effective in improving motor impairments in children with intellectual disabilities. This study contributes to the development of physical activity-based interventions as an alternative approach to enhancing motor skills in children with intellectual disabilities in special education settings.